Do changes of rainfall trends affect choice of drainage systems? - Kubiszyn, Katarzyna; Łochańska, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Precipitation is one of the main factors causing surface, linear and landslide erosion. Their influence on erosion processes is determined by such parameters as: precipitation frequency, amount, duration and intensity. These features affect the rate of infiltration and the intensity of surface runoff, and thus the occurrence, course and effectiveness of erosion processes [2, 3, 4]. The aim of research was to analyse the 40-years of rainfall measurements data from the Lubuskie Voivodeship and inspect whether occurring of heavy rains are random events or maybe indicate some long period trends.
Keywords: precipitation trends; local precipitations; Mann-Kendall test; slope stability; dewatering systems; decision-making process map; opady lokalne; trendy opadów; test Manna-Kendalla; stateczność zboczy; systemy odwadniania; mapa procesu decyzyjnego